Indoor Air Quality and Indoor Environmental Quality: The role of occupational health surveillance and the cooperation between public and occupational health stakeholders - Francesco Chirico; Gaetano Settimo; Nicola Magnavita (Journal of Health and Social Sciences)
This viewpoint emphasizes the growing significance of Indoor Air Quality (IAQ) in improving health and comfort in indoor environments, a crucial concern given that individuals spend approximately 90% of their time indoors. It conducts a comprehensive review of IAQ, highlighting its profound impact on overall health and quality of life, often exceeding outdoor environmental pollution. Our paper identifies various risks associated with IAQ, particularly for vulnerable groups such as children, the elderly, and those with chronic health conditions. It details the dual nature of indoor pollutants—external sources like traffic, heating and cooling of buildings, industrial emissions, and internal sources including combustion for food preparation and heating, building materials and furnishing, paints, cleaning products materials, and human activities. These pollutants, ranging from very volatile organic-VVOC, volatile-VOC, semi-volatile organic-SVOC compounds, particulate matter-PM10, PM2.5, and biological entities, necessitate extensive interdisciplinary research. The viewpoint discusses the severe implications of IAQ, especially in developing countries, where it contributes significantly to the global disease burden. It introduces the concept of Indoor Environmental Quality (IEQ), expanding the focus from just air quality to encompass lighting, acoustics, thermal comfort, and water quality. This holistic approach to IEQ is vital for ensuring health and well-being in indoor spaces. Furthermore, the paper explores the interconnection between IAQ and global health crises, such as climate change and the COVID-19 pandemic, and emphasizes the importance of maintaining good IAQ and visual and thermal comfort in workplaces. These factors are linked to improved health, productivity, and sustainable practices. The role of occupational stakeholders, employers, and medical professionals in creating a healthy work environment is critically examined. We argue for their collaboration in promoting health initiatives, ergonomic designs, and effective health surveillance. This collective approach aims to address the complexities of modern workplaces, fostering a healthier, more productive, and sustainable workforce.